Molecular Mechanisms of Colistin Resistance in Klebsiella pneumoniae Causing Bacteremia from India—A First Report - Pragasam, Agila K.; Shankar, Chaitra; Veeraraghavan, Balaji; Biswas, Indranil; Nabarro, Laura E. B.; Inbanathan, Francis Y.; George, Biju; Verghese, Santhosh (Frontiers in Microbiology, 2017)
Colistin has long been a reserve drug used for the treatment of carbapenem resistant Klebsiella pneumoniae. Carbapenem resistance in K. pneumoniae has been increasing and is as high as 44% in India. Although a reserve agent, with rise in rates of resistance to carbapenems, the usage of colistin has increased over the years leading to slow emergence of resistance. Colistin resistance is mainly mediated by the alteration in the LPS of bacterial outer membrane with the addition of L-Ara4-N and PEtN molecules. These alterations are mediated by mutations in several genes involved in lipidA modifications and most commonly mutations in mgrB gene has been reported. Recently there is emergence of plasmid mediated resistance due to mcr-1 and mcr-2 genes which poses a threat for the rapid global spread. This study aims at characterizing eight colistin resistant K. pneumoniae from bacteremia by whole genome sequencing. Eight K. pneumoniae were isolated from blood culture during 2013 and 2014 at the Department of Clinical Microbiology, Christian Medical College, India. Antimicrobial susceptibility testing was performed and minimum inhibitory concentration (MIC) was determined for colistin and polymyxin B by broth-micro dilution method. Whole genome sequencing was performed using Ion Torrent and the genome of all eight isolates was analyzed. The eight isolates were resistant to all the antimicrobials expect tigecycline. MIC of colistin and polymyxin B were ranged from 4 to 1024 μg/ml and 0.5 to 2048 μg/ml respectively. Multiple mutations were observed in the chromosomal genes involved in lipid A modifications. mcr-1 and mcr-2 gene was absent in all the isolates. The most significant were mutations in mgrB gene. Among the eight isolates, four, three and one were belonged to sequence types ST 231, ST14 and ST147 respectively. Seven isolates had blaOXA−48 like, one co-expressed blaNDM−1 and blaOXA−48 like genes leading to carbapenem resistance. Overall, multiple numbers of alterations have been observed. This includes silent mutations, point mutations, insertions and/or deletions. Mutations in mgrB gene is responsible for resistance to colistin in this study. Due to emergence of resistance to reserve drugs, there is a need for combination therapies for carbapenem resistant K. pneumoniae and colistin must be judiciously used.